PENGARUH CONTENT MARKETING, SISTEM CASH ON DELIVERY (COD) DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA TIKTOK SHOP DI KOTA BOGOR - Mujito; Muhlis; Wawan Hari Subagyo; Yuliyanti (Institut Teknologi dan Bisnis Dewantara, 2026)
This study investigates the influence of Content Marketing, Cash On Delivery (COD) system, and Online Customer Review (OCR) on purchasing decisions for products on TikTok Shop in Bogor City. Rapid advancements in digital marketing, particularly the rise of social commerce platforms like TikTok Shop, underscore the importance of these factors. Using a quantitative method with a causality approach, the research involved a sample of 100 respondents who had made transactions on TikTok Shop in Bogor. Data analysis employed validity tests, reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that Content Marketing (t-count=4.824, sig=0.000), COD system (t-count=2.834, sig=0.006), and Online Customer Review (t-count=8.038, sig=0.000) all positively and significantly affect Purchasing Decisions partially. Simultaneously, all three variables significantly influence Purchasing Decisions (F-count=72.153, sig=0.000). The most dominant factor is Online Customer Review. The coefficient of determination (R2) is 0.683, meaning 68.3% of the variation in Purchasing Decisions is explained by these three variables.